THE PUBLIC ACCOUNTANT SPECIALISTS TO GO ABOUT AS A WAQF PROMISE DEED OFFICIAL (PPAIW) IN LIGHT OF THE WAQF REGULATION - Ginting, Gloria Gita Putri; Aulia, Aulia; Aningrum, Dilla; Sari, Ayu Kurnia (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
Waqf is one of the legal acts that have been around for a long time and are still in use in society. Its rules are not complete and are still scattered across a number of different laws and regulations. The ratification of the nazhir legal entity is related to the Notary's role in the waqf legal actions that have been ongoing thus far. The purpose of this research is to ascertain the Authority of a Notary to act as the Official for Making Waqf Pledges (PPAIW) and the implementation of the making of the Waqf Pledge Deed by a Notary who acts as the Official for Making Waqf Pledges (PPAIW). Descriptive research is the focus of this study. Descriptive research aims to accurately describe an individual, a condition, a symptom, or a particular group, as well as to ascertain the spread of a symptom and whether there is a connection between symptoms and other symptoms in society. As stated in the explanation of the provisions of the Law on Notary Position Number 2 of 2014 Concerning Amendments to Law Number 30 of 2004 Concerning Notary Position, implementation of making the Deed of Waqf Pledge carried out by a Notary as PPAIW